The Effect of Distributed Zakat on Sustainable Economic Development in Indonesia: A VECM Approach - Hamadou, Issa; Mamadou Salieu Jallow (EkBis: Jurnal Ekonomi dan Bisnis, 2024)
The purpose of this article is to examine how Indonesian sustainable economic development factors are affected by distributed zakat. in particular the poverty rate, the human development index (HDI), and economic growth. Time series data from 2001 to 2020 were processed using a vector error correction model (VECM). Additionally, the stationarity and long-run connection have been tested using the unit root and co-integration tests, respectively. The analysis made the assumption that dispersed zakat will have a positive, long-term influence on sustainable economic development. As a result, the main goals of zakat distribution, which are linked to long-term zakat funds and economic expansion, will be effectively accomplished. The case study of only one nation, Indonesia, is one of the research's limitations; therefore, in order to generalize the findings, it is advised that more nations be included in future studies. To help zakat organizations optimize their collecting and distribution strategies, the Indonesian government ought to enact tax reduction programs for them. Furthermore, it is advised that zakat institutions broaden their distribution to include those who are more at-risk in order to significantly reduce poverty and promote sustainable development. There aren't enough empirical findings about the SDGs and zakat. This article, on the other hand, is original and evaluated the dynamic short- and long-term effects of distributed zakat on Indonesia's economic growth, poverty rate, and Human Development Index (HDI).